2009
DOI: 10.1080/10789669.2009.10390864
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Energy Recovery by a Pelton-Type Expander in a Domestic Refrigeration System

Abstract: A Pelton-type two-phase expander was developed to replace the throttling valve for energy recovery in a domestic vapor-compression refrigeration system. The Pelton-type expander was designed and fabricated based on thermodynamic and mathematical analysis. It consists of two Laval nozzles and one simplified twin-arc blade impeller. A combined expander-generator prototype was validated in a R-410A domestic refrigeration system and demonstrated a stable operation within a wide speed range of up to 26,500 rpm. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The maximum efficiency was 15.8% and the output power was 32.7 kW. He et al [18] presented twin arc blade impeller for a Pelton type TPIT using R410a as the working fluid. Experimental results showed that the peak efficiency was 32.8% and the maximum rotational speed was 26500 rpm.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum efficiency was 15.8% and the output power was 32.7 kW. He et al [18] presented twin arc blade impeller for a Pelton type TPIT using R410a as the working fluid. Experimental results showed that the peak efficiency was 32.8% and the maximum rotational speed was 26500 rpm.…”
Section: Introductionmentioning
confidence: 99%
“…He et al. 10 coupled a Pelton-type expander with a centrifugal auxiliary compressor and tested the expander-compressor unit in a domestic air conditioning system using HFC-410A as working fluid and reported increases in COP and cooling capacity by 5.4% and 6.5%, respectively. Mahmoud et al.…”
Section: Introductionmentioning
confidence: 99%
“…The reported maximum turbine efficiency of the single stage turbine expander driven by HCFC-22 two-phase mixture was 52.4% at rotor speed of 1880 r/min and mass flow rate of 1.339 kg/s. He et al 10 coupled a Pelton-type expander with a centrifugal auxiliary compressor and tested the expandercompressor unit in a domestic air conditioning system using HFC-410A as working fluid and reported increases in COP and cooling capacity by 5.4% and 6.5%, respectively. Mahmoud et al 11 proposed comprehensive models regarding the frictional and internal leakage losses of a rotary vane expander in conventional vapor compression refrigeration system without estimating the cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this loss, two phase energy recovery expanders [1][2][3][4][5][6][7][8] or ejectors [9][10][11] replacing the throttling valve have been widely investigated. Flashing flow nozzles are the core part of the impulse turbo expander [12][13][14] or ejector. In the nozzles, the potential energy of the incoming high-pressure subcooled or saturated liquid flow is converted to the kinetic energy of the exiting liquid-vapor flow.…”
Section: Introductionmentioning
confidence: 99%